The Effect of Short-Term Wingate-Based High Intensity Interval Training on Anaerobic Power and Isokinetic Muscle Function in Adolescent Badminton Players - Duk-Han Ko; Yong-Chul Choi; Dong-Soo Lee (Children, 2021)
Badminton requires both aerobic fitness and anaerobic ability for high performance. High intensity interval training (HIIT) is a traditional training method for improving fitness. In this study, we investigated whether short-term Wingate-based HIIT is effective for improving anaerobic activity in youth badminton players. Participants included 32 total badminton players in middle school and high school. They were divided into two groups (HIIT and moderate continuous training (MCT)). Training occurred for 4 weeks in total, three times a week, for 30 min each session. A body composition test, isokinetic knee muscle function test (60°/s, 240°/s), Wingate anaerobic power test (30 s × 5 sets), and analysis of heart rate changes were undertaken before and after training. After 4 weeks, body fat decreased in the HIIT group (p = 0.019); they also showed superior anaerobic ability compared to the MCT group. Differences were statistically significant in 3–4 sets (three sets, p = 0.019; four sets, p = 0.021). Regarding fatigue, the HIIT group showed superior fatigue improvement after training and better fatigue recovery ability in 3~5 sets (three sets, p = 0.032; four sets, p = 0.017; five sets, p = 0.003) than the MCT group. Neither group exhibited changes in heart rate during the anaerobic power test after training. Both groups improved in terms of isokinetic knee muscle function at 60°/s with no differences. However, at 240°/s, the HIIT group showed a statistically significant improvement (p = 0.035). Therefore, HIIT for 4 weeks improved the athletes’ performance and physical strength.